Maternal High-Fat Diet Programs Renal Peroxisomes and Activates NLRP3 Inflammasome-Mediated Pyroptosis in the Rat Fetus - Zhou P (Dove Medical Press, 2021)
Pei Zhou,* Hongbo Guan,* Yanyan Guo, Liangliang Zhu, Xiaomei Liu Key Laboratory of Maternal-Fetal Medicine of Liaoning Province, Department of Obstetrics and Gynecology, Shengjing Hospital of China Medical University, Shenyang, 110004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaomei LiuKey Laboratory of Maternal-Fetal Medicine of Liaoning Province, Department of Obstetrics and Gynecology, Shengjing Hospital of China Medical University Shenyang, 110004, People’s Republic of ChinaTel +86-18940255055Email liuxm@cmu.edu.cnPurpose: Maternal obesity impairs kidney development and function of the offspring and leads to a greater risk of kidney disease in adulthood. The present study aimed to investigate the link between peroxisomes, oxidative stress (OS), and inflammasomes in the fetal kidney of maternal obesity rats and to explore the potential therapeutic effects of the antioxidant pyrroloquinoline quinone (PQQ).Methods: Maternal obesity rats were developed by administration of a high fat diet plus supplementation with PQQ (40 mg/kg body weight) as a potential therapy. Renal histology was observed by Periodic Acid-Schiff staining. The expression profiles of peroxins, fatty acid β-oxidation enzymes, antioxidants, and the regulators of the unfolded protein response (UPR) pathway and NLRP3 inflammasome were analyzed in the kidneys and tubular epithelial cells (TECs) from near-term fetuses (embryonic day 20).Results: The present work revealed that: 1) a maternal high fat diet (MHF) led to higher blood pressure in adult offspring; 2) MHF led to downregulation of peroxisome markers PEX3 and 14 in fetal kidneys; 3) the antioxidant SOD2 and catalase were decreased, and oxidative stress marker Ephx2 was increased; 4) MHF-induced activation of the UPR pathway; 5) the KEAP1-NRF2 pathway was activated; 6) activation of the NLRP3 inflammasome led to secretion of pro-inflammation factors; 7) in TECs, the changes in PEXs and NLRP3 are similar to tissues, but UPR and NRF2 pathways showed opposite trends; 8) and the antioxidant PQQ alleviated maternal lipotoxicity by decreasing ROS levels and inhibiting activation of ER stress and inflammasome in fetal kidney.Conclusion: A maternal high fat diet decreased the number of peroxisomes, subsequently activated OS and inflammasomes, resulting in pyroptosis and apoptosis in fetal kidney. The antioxidant PQQ served a protective role against the effects of lipotoxicity on kidney programming and, thus, is a potential candidate to prevent maternal obesity-induced renal programming.Keywords: maternal obesity, kidney, peroxisome, oxidative stress, inflammasome